Dynamic analysis of base-isolated and fixed-base RC frame buildings under near-field and far-field earthquakes - Patel D.; Kumar R. (My University, 2025)
Earthquakes pose significant risks to buildings and the safety of occupants, often causing severe structural damage. To mitigate these risks, sustainable infrastructure techniques like base isolation are proposed. Base isolation represents an innovative strategy to protect multi-story reinforced concrete (RC) structures from seismic and dynamic loads, addressing potential weaknesses under such conditions. This study compares the responses of an RC frame building with base isolation to those of a fixed-base structure when subjected to seven near-field (NF) and seven far-field (FF) earthquake records from the Imperial Valley, Loma Prieta, Northridge, Kobe, ChiChi, Chamoli and Uttarkashi earthquakes. The High Damping Rubber Bearings (HDRB) and Lead Rubber Bearings (LRB) are used as seismic isolator device in the building. Using SAP2000, a base-isolated (BI) building model was created and subjected to non-linear time history (NLTH) analysis to simulate responses during NF and FF earthquake events. Ground motions were matched to IS 1893 Part 1 (2016) using SeismoMatch software, specifically focusing on seismic events in zone V. The analysis evaluated the buildings responses under these matched ground motion inputs, providing insights into the efficiency of the BI system in diminishing seismic forces. Results showed that base isolators effectively absorb seismic energy, resulting in significant reductions in base shear, top floor displacement, absolute joint acceleration for each story, and peak base displacement for both NF and FF events. These findings demonstrate the potential of BI to augment the seismic capacity of buildings in earthquake-prone regions. © Indian Academy of Sciences 2025.